First report of mecC gene in clinical methicillin resistant S. aureus (MRSA) from tertiary care hospital Islamabad, Pakistan. Issue 10 (October 2020) - Khan, Amir Afzal; Ali, Asad; Tharmalingam, Nagendran; Mylonakis, Eleftherios; Zahra, Rabaab
Abstract: Background: Staphylococcus aureus ( S. aureus ) is one of the leading causes of community and hospital acquired infections globally. The objective of the study was to assess the prevalence, study the carriage of antibiotic resistance genes and evaluate the molecular typing of S. aureus isolates from a tertiary care hospital in Islamabad. Methods: A total of 1528 staphylococci isolates were included in this study. Standard microbiological procedures were applied to identify S. aureus . Antimicrobial susceptability was evaluated using the disk diffusion method and Minimum Inhibitory Concentrations (MICs) were determined using microbroth dilution method following Clinical and Laboratory Standards Institute (CLSI) guidelines. Multiplex PCR was used to detect antibiotic resistance genes, and molecular typing was performed using agr, SCC mec, spa, and Multi-Locus Sequence Typing (MLST) and clonal relatedness by Pulse Field Gel Electrophoresis (PFGE) methods. Results: Overall 65% were MRSA and 35% were methicillin sensitive Staphylococcus aureus (MSSA). Among MRSA isolates, 83% were multi-drug resistant and mec A was found in 54% isolates, mec C was in 3% while 1 MRSA carried both mec A and mec C genes. agr I (22%) was most prevalent group in MRSA, while agr III (16%) was observed in MSSA. SCC mec types I, II, III, IV, and VI were detected, with high prevalence of type III while type V was absent. The prevelant spa type in MRSA was t657 with SCC mec III elelments while in MSSA it was t021. One NEW spa type identified in MSSA isolates. In a subset of isolates, ST772 with SCC mec IV, ST1 carrying PVL marker, and ST1535 was reported first time from Pakistan. Conclusions: The study presents a comprehensive analysis of prevalent S. aureus types and their antibiotic resistance profiles. It also reports for the first time SCC mec type VI and clinical MRSA isolates with mec C alone and in combination with mec A from Islamabad, Pakistan. This calls for further detailed investigations in other hospital settings in the region.